Enhancing ketones and syngas production by CO2-assisted catalytic pyrolysis of cellulose with the Ce–Co–Na ternary catalyst. (1st July 2022) - Jiang, Haifeng; Liu, Haipeng; Dong, Jiaxin; Song, Jiaxing; Deng, Sunhua; Chen, Jie; Zhang, Yu; Hong, Wenpeng
Abstract: Using cellulose to produce high-quality oxygenated fuels or chemicals is becoming an important way to replace chemical synthesis technology. In this work, the Ce–Co–Na ternary composite metal catalyst is synthesized and used for catalytic cracking of cellulose to prepare the ketone-rich bio-oil production. To construct an environment-friendly process, CO2 is used as a pyrolysis reaction atmosphere to improve the enrichment of ketones. Strong synergistic effects among metal components effectively promote the thermal-cracking of cellulose to produce primary products (anhydrosugars), and further convert to oxygenates due to the excellent oxygen transferability of the catalyst. The introduction of CO2 enhances the selectivity of ketones in the liquid product, especially 2, 3-dimethyl-2-cyclopenten-1-one. The highest content of ketones in the liquid is 22.73%, which is about four times higher than that of the blank sample. In addition, the generation of CO in the syngas is promoted. This study provides an alternative way for the pyrolysis of biomass to prepare ketone platform compounds and syngas production. Highlights: A catalyst that can effectively promote cellulose decomposition is synthesized. The high selectivity of ketones is obtained by CO2 -assisted catalytic pyrolysis. The optimal conditions for producing ketones and syngas are given. A brief reaction pathway of CO2 -assisted catalytic pyrolysis of cellulose is shown.